Evaluation of the efficacy and tolerability of naftidrofuryl in the therapy of chronic cerebral ischemia - M. N. Dadasheva; I. A. Zolotovskaya; R. V. Gorenkov; K. N. Dadasheva; D. I. Lebedeva (Неврология, нейропсихиатрия, психосоматика)
Objective: to study the clinical efficacy and tolerability of naftidrofuryl (Duzofarm®) in patients with chronic cerebral ischemia (CCI).Patients and methods. A prospective open-label multicenter observational study evaluated the clinical efficiency and tolerability of naftidrofuryl treatment in patients with CCI. To statistically evaluate the efficacy and tolerability of naftidrofuryl, the investigators used data from 200 outpatients with Stages I–II CCI who were included in the program of treatment and received its full cycle. The patients were prescribed naftidrofuryl at a dose of 100 mg (2 tablets) thrice daily. Basic therapy that the patients had received before their inclusion in the observation program was not discontinued. The patients' status was evaluated using a specially designed questionnaire. Four visits were scheduled. All the patients underwent neurological examination. To study the patients' cognitive functions and emotional state, the investigators used the following tests and scales: the Mini-Cog test, the Mini-Mental State Examination (MMSE), the Zung Self-Rating Anxiety Scale, the Asthenia Subjective Assessment Scale, and the Modified Scoring Scale for Subjective Sleep Characteristics. Adverse reactions were recorded to evaluate the tolerability of therapy.Results and discussion. Naftidrofuryl therapy significantly improved health and reversed complaints in the patients. By the end of the treatment cycle, there was a significant improvement on all scales, which suggested a decrease in the severity of cognitive impairment and asthenic and mild anxiety disorders. When performing the Mini-Cog test, the proportion of patients who were able to remember and recall three words without errors increased from 43 to 86%, and when doing the clock drawing test, the proportion increased by 65%. Cognitive functions on the MMSE were observed to statistically significantly improve by 1.2 scores. According to the Zung Anxiety Self-Rating Scale, the number of patients with anxiety disorders decreased by 24%, those with insomnia significantly declined by 31% compared with the baseline level.Conclusion. The findings showed the high efficiency and appropriateness of naftidrofuryl administration to patients with Stages I–II CCI and hypertension.